Testing of the high- density polyethylene pipes for transporting the natural gas (Journal of Humanitarian and Applied Sciences, 2023)
The purpose of this study is to prove that the polyethylene pips (PE) can be used instead of the carbon Steel pipes (CS) for the reason of the natural gas transportation. Since 1960’s, the (CS) was in use for crude oil as well as water and natural gas transport from point to point, in which it was manufactured by many ways whereas wrapping the sheets of steel to the shape of the pipes using rolling machine then weld them to have a pipe in the final stage. The whole manufacturing process is expensive and determines the working life of the pipelines for many reasons whereas the corrosion and resistance are the important ones. Moreover; the maintenance of the buried (CS) pipelines was needed from time to time to prevent leakage and maintain cathodic protection to soil resistance which add extra cost and limits, the age, of the pipes. The manufacturing process of the PE pipes is cheaper simpler, than (CS) as well as the lifetime of PE is longer than the (CS) which reaches up to 50 years of use, also it sufficient and less wight than the (CS) ones, in addition, it doesn’t need the maintenance that the (CS) pipes needs. Therefore, this research has proven that the PE can be used PE 100, for the purpose of the natural gas transportation based on the result obtained which has been taken and even has been experimenting the pressure limits (operation pressure) internally and externally by using the finite elements software (Solid-Work) which simulates the internal stresses in the pipes and external loads on it.
Keywords: transporting; natural gas; Testing; high- density